2012
DOI: 10.1051/0004-6361/201219390
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen oxides and carbon chain oxides formed after ion irradiation of CO:N2ice mixtures

Abstract: Context. High CO depletion as well as depletion of N-bearing species is observed in dense pre-stellar cores. It is generally accepted that depleted species freeze out onto dust grains to form icy mantles and that these ices suffer energetic processing due to cosmic ion irradiation and ion-induced UV photons. Aims. The aim of this work is to study the chemical and structural effects induced by ion irradiation on different CO:N 2 mixtures at low temperature (16 K) to simulate the effects of cosmic ion irradiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 70 publications
3
49
0
Order By: Relevance
“…These doses are sufficient to alter the chemical composition. Based on the present results, NO, NO 2 and N 2 O are formed (note that nitrogen oxides are also formed after ion bombardment of mixtures containing nitrogen and carbon monoxide, Sicilia et al 2012). We suggest here that the measurement of molecular ratios NO/NO 2 and NO/N 2 O in the ice and/or in the tenuous atmospheres of those objects are useful to confirm the presence of nitrogen and reveal if oxygen is present as well.…”
Section: Ices In Solar System Objectssupporting
confidence: 64%
“…These doses are sufficient to alter the chemical composition. Based on the present results, NO, NO 2 and N 2 O are formed (note that nitrogen oxides are also formed after ion bombardment of mixtures containing nitrogen and carbon monoxide, Sicilia et al 2012). We suggest here that the measurement of molecular ratios NO/NO 2 and NO/N 2 O in the ice and/or in the tenuous atmospheres of those objects are useful to confirm the presence of nitrogen and reveal if oxygen is present as well.…”
Section: Ices In Solar System Objectssupporting
confidence: 64%
“…However, reactions (10) and (11) are potentially still limited by the interstellar low abundance of the parent species. Finally, nitrogen-bearing acids, like nitrous acid and nitric acid, can be formed through surface reactions (7) and (8). Although the formation of these acids was not verified here, their interstellar relevance should not be excluded.…”
Section: Astrophysical Implicationsmentioning
confidence: 81%
“…When carbon-bearing species are present in the ice that are irradiated with a mixture containing N 2 , OCN À is also formed. 7,8 Laboratory studies of non-energetic surface processing showed that, for instance, ammonia (NH 3 ), hydroxylamine (NH 2 OH), nitrogen dioxide (NO 2 ), dinitrogen trioxide (N 2 O 3 ), nitrous acid (HNO 2 ), and nitric acid (HNO 3 ) are efficiently formed at low temperatures through hydrogenation of N-atoms, NO + H, NO + O 2 , NO + NO 2 , NO + OH, and NO 2 + OH reactions, respectively. [9][10][11][12][13][14][15][16] In the accompanying paper, hereafter referred to as Part I, 17 we investigate the oxygenation of solid NO (NO + O/O 2 /O 3 ) at a Division of Geological and Planetary Sciences, California Institute of Technology,…”
Section: Introductionmentioning
confidence: 99%
“…This is because CO 2 is not in a pure ice but is mixed with other species, such as carbon chain oxides formed after ion irradiation (see e.g. Palumbo et al 2008), and is trapped in a refractory residue also formed at low temperature after ion irradiation (Sicilia et al 2012). The experiment shown in the top-right panel of Fig.…”
Section: Irradiation Of Ice Mixturesmentioning
confidence: 99%